2014
DOI: 10.16943/ptinsa/2014/v80i1/55094
|View full text |Cite
|
Sign up to set email alerts
|

EMS Induced Mutants of Upland Rice Variety Nagina22: Generation and Characterization

Abstract: One of the approaches for understanding the functions of the genes predicted in the rice genome requires use of mutants. Mutations induced in a given genetic background provide opportunities to assign function to a given gene with a minimum of background genetic noise. This paper describes generation and initial characterization of a large set of Ethyl Methane Sulphonate (EMS) induced mutants in the upland rice variety Nagina22, through a National Initiative involving six Research Institutes namely National Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 21 publications
8
63
0
2
Order By: Relevance
“…Use of chemically induced mutants such as ethyl methane sulfonic acid (EMS) has helped to create useful genetic variations in the past (Bhat et al, 2007;Till et al, 2007;Henry et al, 2014;Mohapatra et al, 2014). It has been shown that mainly GC to AT transitions were induced by EMS in Arabidopsis, maize and wheat, (Till et al, 2003;Till et al, 2004;Slade, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Use of chemically induced mutants such as ethyl methane sulfonic acid (EMS) has helped to create useful genetic variations in the past (Bhat et al, 2007;Till et al, 2007;Henry et al, 2014;Mohapatra et al, 2014). It has been shown that mainly GC to AT transitions were induced by EMS in Arabidopsis, maize and wheat, (Till et al, 2003;Till et al, 2004;Slade, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nagina 22 is a well-known aus variety used routinely as a check for heat tolerance in rice (Jagadish et al, 2010). In a network project, EMS-induced stabilized N22 mutants were evaluated for different traits, such as tolerance to herbicide, heat, low P, water deficiency, and salinity and resistance to bacterial leaf blight and blast (Kulkarni et al, 2013(Kulkarni et al, , 2014Lima et al, 2015;Mithra et al, 2016;Mohapatra et al, 2014;Panigrahy et al, 2009Panigrahy et al, , 2011Panigrahy et al, , 2014Poli et al, 2013;Talla et al, 2016). As a part of the network project on functional genomics, a total of 2500 N22 mutants were screened at the Indian Institute of Rice Research (IIRR) under field conditions maintained with low P (Olsen P, <1.8) to identify low-P-tolerant and susceptible mutants.…”
mentioning
confidence: 99%
“…Linkage between the putatively linked marker and the target gene was estimated using genotypic data and the phenotypic data with the help of MAPMAKER v3.0 software (Lander et al 1987). Linkage was considered significant if the Logarithm of Odds (LOD) score was ≥3.0.…”
Section: Methodsmentioning
confidence: 99%